1147PEfficacy and safety of anlotinib for patients with recurrent and/or metastatic salivary gland carcinomas. (1st October 2019) - Jiang, W; Dou, S; Li, R; Zhang, L; Zhu, G
Abstract: Background: Pre-clinical and clinical evidence suggests a rationale for the use of anti-angiogenic agents in recurrent and/or metastatic salivary gland carcinomas (RMSGCs). This study evaluates the activity the efficacy and safety of anlotinib, a novel vascular endothelial growth factor receptor (VEGFR) inhibitor in patients with RMSGCs. Methods: In this single-arm phase II study, patients with RMSGCs were treated with anlotinib 12mg QD p.o. until disease progression, intolerable toxicity or withdrawal of consent. The primary endpoint was the objective response rate (ORR). Progression-free survival (PFS), overall survival (OS), and adverse events were also assessed. This study had been registered with ClinicalTrails. gov: NCT 03591666. Results: Between June 2018 and February 2019, 24 patients with RMSGCs were screened and 21 patients were enrolled in this study. 10 patients (47.6%) were male, and the median age was 54 years (range 29-75). The most common histologic type was adenoid cystic carcinoma (52.4%), which was followed by adenocarcinoma (19.0%). 16 patients (76.2%) were treated as third-line or further treatment. The objective response rate was 19.1% (95%CI 5.4%-41.9%). The disease control rate was 81.0% (95%CI 58.1%-94.6%). One patient died due to the progress of the disease. At the time of the data cutoff, with a median follow-up of was 4.8 months (range 0.9-9.3), the median PFS had not been reached, and the PFS rate at 6 months was 78.9% (95% CI, 58.1%-94.6%). No drug-related mortality occurred. The most common clinically significant grade 3 or higher adverse events were hypertension (28.6%) and hand-foot syndrome (9.5%). Conclusions: Anlotinib showed a high disease control rate in patients with RMSGCs. The toxicity was tolerable and manageable. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.